1999
DOI: 10.1002/(sici)1097-0290(19990805)64:3<290::aid-bit5>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-modified ligninase enhances pentachlorophenol biodegradation in water-solvent mixtures

Abstract: Polychlorinated hydrocarbons are prevalent environmental contaminants whose rates of biodegradation are limited by their minimal solubilities in aqueous solutions where the biological reactions take place. In this study, ligninase (LiP) from Phanerochaete chrysosporium was modified by poly(ethylene glycol) to enhance its activity and stability for the biodegradation of pentachlorophenol (PCP) in the presence of acetonitrile (MeCN), a water-miscible solvent. The modified enzyme retained 100% of its activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In many cases, however, low catalytic efficiency and stability of enzymes have been seen as barriers for the development of largescale operations to compete with traditional chemical processes (1)(2)(3)(4)(5)(6). Methodologies such as genetic and protein engineering (7-10), evolution (11,12), solvent engineering (2,(13)(14)(15), and chemical modification (16)(17)(18)(19)(20)(21) are among the most actively investigated strategies to improve the functionality and performance of enzymes for bioprocessing applications.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, however, low catalytic efficiency and stability of enzymes have been seen as barriers for the development of largescale operations to compete with traditional chemical processes (1)(2)(3)(4)(5)(6). Methodologies such as genetic and protein engineering (7-10), evolution (11,12), solvent engineering (2,(13)(14)(15), and chemical modification (16)(17)(18)(19)(20)(21) are among the most actively investigated strategies to improve the functionality and performance of enzymes for bioprocessing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with intact cells of P. chrysosporium , degradation of lignin or organopollutants using lignin degrading enzymes, such as LiP, MnP, and laccase (phenol oxdiase), has some advantages, including no nutrient supply and easy control of temperature and pH [12], however, this enzymatic degradation is influenced by the H 2 O 2 supply strategy. At the beginning of the reaction, activity of Lip or MnP is inhibited by excess H 2 O 2 .…”
mentioning
confidence: 99%
“…MALDI-TOF analyses of the conjugate samples unfortunately failed to reveal the molar mass of the conjugate. Conversely, MALDI-TOF analyses of CT conjugated with an amphiphilic modifier, PEG (M w 5000), indicated that one or two attachments were achieved (10). Since the conjugate of PS (water insoluble) in the current work involved a much weaker reaction as compared to that of PEG (water soluble), we believed that the majority of conjugate should only have one PS chemically attached to each CT molecule.…”
Section: Resultsmentioning
confidence: 77%